Pancasila dan Korupsi - Nurhalizah, Siti (Maliki Interdisciplinary Journal, 2025)
This paper is a study on how Pancasila as the basis of the state and efforts to eradicate corruption in Indonesia are related to each other. Pancasila, which consists of five precepts, contains ethical and moral principles that underlie national and international life. However, these values are at odds with rampant corrupt practices in various sectors. In this paper, it is described how each precept of Pancasila is relevant in fighting corruption, both through the application of the values of Godhead, Humanity, Unity, People, and Social Justice. The paper also identifies the factors that lead to corruption, such as social tolerance for corrupt practices, weak legal systems, and a lack of understanding of social justice. In addition, it was explained that policies such as digitalization, regulatory synchronization, and empowerment of human resources show the role of the government. It is recognized that the role of the people is very important to supervise, report, and cooperate with anti-corruption forums. Greater enlightenment is needed to combat corruption and strengthen the application of Pancasila in daily life through anti-corruption education based on Pancasila values.